Pengabdian Kepada Masyarakat Cerdas Mengenal Dan Mencegah Penyakit Menular Pada Sistem Pernapasan (TBC) Dari Segi Epidemiologi Di Kalangan Remaja - Huwaina Af’idah; Soeharto; Nofi Susanti; Andini Br Sembiring; Bela Wahyuni Manurung (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Tuberculosis (TB) is a contagious disease of the respiratory system that remains a global public health problem, including in Indonesia, with high incidence rates among adolescents due to intense social activities and interactions. This community service activity aims to increase adolescents' knowledge about TB from an epidemiological perspective, including modes of transmission, symptoms, risk factors, and prevention efforts as an airborne disease. The method used was a quasi-experimental approach with a two-group pretest-posttest design, through health education provided to 149 adolescents aged 15–17 years at Darussalam High School in Medan. Data collection was conducted using questionnaires to assess the level of knowledge before and after the educational intervention. The results of the activity showed a significant increase in the level of knowledge after the education was provided, where the percentage of respondents in the high knowledge category increased from 82% in the pre-test to 93% in the post-test, accompanied by a decrease in the sufficient and low knowledge categories. This study shows that community service activities through health education have a significant effect on increasing adolescents' knowledge about tuberculosis. Health education has been proven to be effective as a promotional and preventive measure, so it needs to be implemented continuously to prevent the transmission